(3eSGFd aj GdejQGKs - (3GdeGebGfj, YHO Gddg Hf eMeO MSf, J (B1351 (3g`s ((3HNW eDdagGs)
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg QH GdYGdejf(B...(3hHYO abO SCd HYV Cgd LjdGf efP SJI CTgQ HYV CYGXe GdWGFaI(B...s
(3BNQgG (B:s
(3GdKGdKI Cfj EfeG de CHjf GSej aj Chd GdQSGdI hdG BNQgG deG QCjJ ef (B... (3YOe JCed CYdGe GdYUQ aj cdeGJj deG GSJbQ Ydjg OCHge hLQJ Ydjg YGOJge(B...(3hGddg NjQ eYhd heCehd hCLd ef jVQ efg GdQO hjfaY efg GdbHhd(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B133s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B277s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis